2018
DOI: 10.1177/0265407517748791
|View full text |Cite
|
Sign up to set email alerts
|

Ghosting and destiny: Implicit theories of relationships predict beliefs about ghosting

Abstract: Two studies examined how implicit theories of relationships are associated with ghosting (i.e., ending a relationship by cutting off all contact). Previous research on implicit theories of relationships has identified two types of beliefs, destiny and growth, and the present research examines how these implicit theories are associated with ghosting perceptions, intentions, and behaviors. Study 1 was an exploratory study conducted on Mechanical Turk that focused on romantic relationships (N = 554). Study 2 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
127
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(150 citation statements)
references
References 39 publications
10
127
0
13
Order By: Relevance
“…These approaches will be important to advancing what we know about how young people navigate their romantic and sexual experiences. For example, growing attention is being given to the “ghosting” phenomenon (i.e., removing all contact from a romantic partner; Freedman, Powell, Le, & Williams, ) as well as “just talking” as a step in relationship formation (Sibley, Kahovec, Schraufnagel, & Stoffel, ; Sibley et al, ). As technological advances develop and infiltrate growing aspects of young peoples' lived experiences, it will be necessary to develop theory about and gain in‐depth understandings regarding these influences.…”
Section: Methodological Approachesmentioning
confidence: 99%
“…These approaches will be important to advancing what we know about how young people navigate their romantic and sexual experiences. For example, growing attention is being given to the “ghosting” phenomenon (i.e., removing all contact from a romantic partner; Freedman, Powell, Le, & Williams, ) as well as “just talking” as a step in relationship formation (Sibley, Kahovec, Schraufnagel, & Stoffel, ; Sibley et al, ). As technological advances develop and infiltrate growing aspects of young peoples' lived experiences, it will be necessary to develop theory about and gain in‐depth understandings regarding these influences.…”
Section: Methodological Approachesmentioning
confidence: 99%
“…A poll conducted by YouGov and Huffington Post in 2014 surveyed 1000 US adults (52% female, 82% over the age of 30, 79% white), and found that approximately 13% of the responders had previously been ghosted by a partner and 11% reported having ghosted a partner themselves (Moore, 2014). More recently, Freedman et al (2018) found that 25.3% of a sample of 554 participants (49% female, M age = 33.86, SD age = 10.62, 75% white) drawn from Amazon's Mechanical Turk (MTurk) had been ghosted, and 21.7% had previously ghosted a romantic partner. In a second sample from Prolific Academic (N = 747, 46% female, M age = 32.64, SD age = 11.59, 74% white), 23% of participants had experienced being ghosted and 18.9% reported having ghosted a romantic partner.…”
Section: Ghostingmentioning
confidence: 99%
“…Much of the existing ghosting literature has used qualitative data to provide definitions and preliminary descriptive information of the phenomenon (LeFebvre et al 2019;Koessler et al, 2019) and only one study has been published that uses a theoretical perspective to explain when ghosting is used to dissolve a romantic relationship (Freedman et al, 2018). Freedman et al (2018) investigated the association between implicit theories of relationships and ghosting behaviors, intentions, and perceptions.…”
Section: Ghostingmentioning
confidence: 99%
See 2 more Smart Citations